Reaction to Endoplasmic Reticulum Stress via ATF6 in Amyotrophic Lateral Sclerosis Deteriorates With Aging - Prell, Tino; Stubendorff, Beatrice; Le, Thanh Tu; Gaur, Nayana; Tadić, Vedrana; Rödiger, Annekathrin; Witte, Otto W.; Grosskreutz, Julian (Frontiers in Aging Neuroscience, 2019)
Amyotrophic lateral sclerosis (ALS) is a multisystemic neurodegenerative disorder. Because peripheral blood mononuclear cells (PBMC) can serve as ´window to the central nervous system´ we aimed to answer whether endoplasmic reticulum (ER) stress in ALS-PBMCs is related to disease aggressiveness. We studied ER stress in PBMCs of 49 patients with ALS and 31 age- and sex-matched healthy controls. The expression of a main ER stress marker, activating transcription factor 6 (ATF6), was significantly higher in ALS compared to controls, but did not correlate with age, disease severity, disease duration and disease progression rate. When ATF6 expression levels were plotted against rD50-derived disease phases derived from the D50 ALS model, two distinct clusters of patients were observed: cluster 1, with progressively increasing ATF6 expression levels and cluster 2, which demonstrated stable ATF6 expression over the disease course. Individuals in the two clusters did not significantly differ in terms of ALSFRS-R, disease aggressiveness, disease duration and subtype. Using the novel D50 model of ALS progression we detected a cluster with increasing ATF6 levels across continuous disease phases and a cluster with a stable expression level.However, pPatients with the increasing ATF6 level were significantly younger, indicating that aging processes might be related to ER stress in ALS. Our data suggest that the reaction to ER stress during disease course may be diminished in older patients with ALS.